Tradisi Tabuik sebagai Kegiatan Tahunan di Pariaman Sumatera Barat - Abdul Gani Jamora Nasution; Putri Azkia; Zulfa Zakiyyah; Anggun Asri Winarti; Zahratunnisa Zahratunnisa (Journal on Education, 2023)
The tabuik tradition is now not only as a customary tradition or spiritual tradition for the Pariaman people, but now tabuik is also used as a tool or media to attract tourists. the way it is held has not changed at all and is still the same as before. This study uses a descriptive qualitative method. This research reveals about the tabuik tradition as an annual activity in Pariaman, West Sumatra. Communities living around the coast hold a tabuik tradition to commemorate the death of the grandson of the Prophet Muhammad, named Husenin Bin Ali Bin Abi Talib. The implementation of this tabuik tradition has several stages, starting from the ma'ambiak of the land to the disposal of the tabuik into the sea. Each tabuik framework has its own meaning. And there are 8 tabuik frameworks that have a combination of religious and customary values. Tabuik in the way of implementation experiences differences, this can be seen from the form, the constituent materials, the people who carry out it and the method of implementation